Artificial Intelligence and Employee Engagement: Evidence from Digital HR Practices - Prastiyo Diatmono (PT. Anagata Sembagi Education, 2026)
The digital transformation of human resource management has accelerated the adoption of artificial intelligence (AI) across various HR practices, including recruitment, performance appraisal, and employee development. While AI has been widely recognized for improving efficiency and accuracy in HR processes, its implications for employees’ psychological outcomes, particularly employee engagement, remain underexplored. This study aims to examine the influence of artificial intelligence in digital HR practices on employee engagement. A quantitative explanatory design was employed, involving employees who actively use AI-based digital HR systems. Data were collected through a structured questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). The results indicate that artificial intelligence embedded in digital HR practices has a positive and significant effect on employee engagement. These findings suggest that AI-driven HR systems that emphasize support, personalization, and transparency enhance employees’ cognitive, emotional, and behavioral engagement. This study contributes theoretically to the digital HR literature by positioning AI as a strategic driver of employee engagement and provides practical insights for organizations seeking to implement human-centered AI in HR management.